The Influence of Trust, Service Quality and Company Image on Savings Customer Loyalty AT PT. BPR Dharma Nagari - Adelia, Riang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2025)
This study was conducted to determine the influence of trust, service quality, and corporate image on savings account customer loyalty at PT. BPR Dharma Nagari. The purpose of this study was to examine and analyze the influence of trust, service quality, and corporate image on savings account customer loyalty at PT. BPR Dharma Nagari. This study used a quantitative research method, with data collected using a questionnaire from March to April 2025. The sample size was calculated using the Slovin formula, with a population of 7,094 respondents. The results showed that trust, service quality, and corporate image had a positive and significant effect on savings account customer loyalty at PT. BPR Dharma Nagari, partially (t-test) and simultaneously (f-test). The R2 value was 0.726, indicating that all independent variables affected the dependent variable by 72.6%, while the remaining 27.4% was influenced by other factors not examined in this study.